A time-saving method to evaluate the thermal insulation performance of cryogenic vessels. (10th June 2020) - Zhang, J.F.; Wei, G.M.; Qu, Z.G.
Abstract: Equivalent mass loss is a critical index used to evaluate the thermal insulation performance of cryogenic vessels. The current test standards for measuring the thermal insulation performance of cryogenic vessels in different countries require a long testing time and waste a considerable amount of working medium. In this study, a method that can shorten the test time of the thermal insulation performance of cryogenic vessels is established. Different from the current test methods that rely entirely on experiments, the method proposed in this paper is a semi-experimental and semi-analytical calculation method. The proposed method is based on the one-dimensional heat transfer analysis of a cryogenic vessel and short-term experimental test data, and it can be used to predict the mass loss over a long period of time. Moreover, the method can predict the mass loss of a cryogenic vessel at a high liquid level when the mass loss at a low liquid level is known. When this method is used to predict the mass loss, the comparison with the experimental data shows that the maximum relative error of the instantaneous mass flow is 21.1% and the relative error of the cumulative mass flow is less than 8%. When this method is used for the calculation of heat leakage between different liquid levels, the results show that the larger the difference between the two liquid levels, the greater the error of leakage heat, and the maximum is 18.9%. Graphical abstract: Image 103672 Highlights: An optimized test method for the insulation performance is presented. A correlative formula between level and heat leakage is established. The method can predict the mass loss of the cryogenic vessel. The proposed method can shorten the test time. The error of this method compared with experiment is below 8%.